Gotas suspensas: uma proposta para amostragem e análise de gases traços da atmosfera - Cardoso, Arnaldo Alves [UNESP]; Pereira, Elisabete A. [UNESP]; Rocha, Julio Cesar [UNESP] (Sociedade Brasileira de Química, 1998)
In the present paper, we report on the analytical use of a dynamic droplet based gas collection and an analysis system. A droplet formed at the tip of a tube represents a sampling approach that provides an indefinitely renewable surface and uses very little reagent. Sample gas flows past the droplet at a low flow rate. After the gas was sampled , the analysis can be carried out by different methodologies. The feasibility of the sensor is demonstrated by continuos determination of gaseous as: NO2, Cl2 and SO2.
Liquid droplet: a proposal for sampling and analysis of trace gas in the atmosphere
Keywords: gases analysis; air analysis; gases sampling